Management of Crush Injury’s Complications Using Hyperbaric Oxygen Therapy: Case Series - Arikalang, Patrick S.; Hatibie, Mendy J.; Oley, Maximillian C.; Noersasongko, Albertus D.; Suharso, Tommy (Universitas Sam Ratulangi, 2024)
Abstract: Crush injury occurs due to an external trauma mechanism that directly affects the skin, muscle, and bone tissue. Crush injuries can involve several parts of the body at the same time. When accompanied by handling, wound healing in crush injury can be long-term, so that it can affect the function of the patient. Various complications that can occur ranging from secondary infection, necrosis, recurrent bleeding, to compartment syndrome. We reported serial cases of crush injury with various clinical presentations and complications, varying in the age range of 16-65 years. All four patients were given multiple managements, such as open reduction external fixation and extensive debridement. There were complications such as secondary infection and delay in the wound healing process in patients who did not on time for follow-up. The four patients received additional treatment in the form of wound dressings hyperbaric oxygen therapy (HBOT) with 5-10 90-minute sessions under 2.4 ATA pressure for 10 consecutive days. Follow-up was carried out again within a period of one month to compare the wound condition before and after HBOT. The clinical condition was getting better, marked by the formation of granulation tissue. The state of hyperoxia in HBOT accelerated the inflammatory process and angiogenesis during the wound healing process characterized by the eradication of bacteria in the wound tissue and accelerated neovascularization formation. In conclusion, adequate therapy, wound dressing, and patient compliance affect patient outcome. Moreover, the addition of hyperbaric oxygen therapy has shown to accelerate the wound healing process and restore the patient's limb function. Keywords: crush injury; hyperbaric oxygen therapy; oxygen; wound healing